Compromisso constitucional com a pacificação: provenção de litígios e tratamento adequado de conflitos empresariais - Bacellar, Roberto Portugal (2023)
The thesis is dedicated to understanding the culture of litigation as opposed to the culture of peace, grounded on the constitutional commitment to pacification as a unifying principle of the adequate treatment of conflicts policy, especially those of a business nature. The research focuses on consensual methods of conflict resolution application in the Brazilian Judiciary and includes an empirical investigation carried out with judge/justices. The aim is to understand how these agents interpret and implement the procedural legislation encouraging mediation and conciliation. It advocates a more active role for judges and a re-signification of their role in cooperative conflict management, together with lawyers and parties to find the appropriate methods and solutions to disputes. Argues that the judge's pedagogical management could weaken the Habitus (a term used by Pierre Bourdieu) of litigiousness that surrounds and involves the judicial field. Therefore, discuss the promotion of methodological instrumental actions, through multiple doors, to achieve the “provention” (according to Burton) of disputes and consensual treatment of conflicts, with a systemic and “exletic” vision (based on De Bono), emancipating entrepreneurs to deal with future conflicts without having to litigate before the Judiciary.